The effect of lavender aromatherapy on primary dysmenorrhea in female students - Ana Mariza; Livia Nizaranuki; Sunarsih Sunarsih; Nurul Isnaini (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Adolescence is marked by the maturation of reproductive organs, including menstruation, which is often accompanied by dysmenorrhea. In Indonesia, the prevalence of dysmenorrhea reaches 55%, and in Lampung it is recorded at 54.9%. Dysmenorrhea impacts activities, learning concentration, and even school attendance. At SMPN 1 Batu Ketulis, 81.2% of female students who visited the health center complained of menstrual pain. Pharmacological interventions such as analgesics have side effects. Non-pharmacological efforts such as lavender aromatherapy are considered effective, safe, and easy. Lavender contains linalool and linalyl acetate, which have relaxant properties. Purpose: to determine the effect of lavender aromatherapy on primary dysmenorrhea in female students. Method: This type of quantitative research uses a pre-experimental research design with a one-group pretest-posttest design. The population of this research isall female students at SMPN 1 Batu Ketulis, West Lampung Regency who experience menstrual pain a total of 86 female students were sampled with 30 respondents using purposive sampling techniques. Data collection used observation sheets, and data analysis was performed using univariate and bivariate methods (Wilcoxon test). Results: The results of this study showed that the average dysmenorrhea in female students before being given lavender aromatherapy was 4.43 and after being given lavender aromatherapy was 1.13. Conclusion: From the results obtained, there was a decrease of around 3.33 so that it can be interpreted that there was a significant effect of giving lavender aromatherapy on primary dysmenorrhea in female students. Suggestion: Suggestions are expected for adolescents to use lavender aromatherapy in reducing menstrual pain